2019
DOI: 10.1016/j.yebeh.2019.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported attitudes about medication in Lebanese people with epilepsy

Abstract: Background: Epilepsy is a common worldwide neurological disorder. For people with epilepsy, adherence and attitudes towards medication is a crucial step to improve efficacy of prescribed treatment and to prevent seizures.Objectives: The first aim of this study was to evaluate attitudes towards antiepileptic medications in Lebanese population. Secondary aims were to assess factors affecting attitudes and associated with epilepsy control.Material and Methods: A cross-sectional study was conducted in out-patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…In addition, DRPs can be related to the behaviors of patients when they take less or more of the drug than prescribed or with inappropriate dosing intervals. In a previous study, positive attitudes towards ASDs in Lebanese PWE were lower, when the treatment was an economic burden, and in depressive people 14 …”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, DRPs can be related to the behaviors of patients when they take less or more of the drug than prescribed or with inappropriate dosing intervals. In a previous study, positive attitudes towards ASDs in Lebanese PWE were lower, when the treatment was an economic burden, and in depressive people 14 …”
Section: Discussionmentioning
confidence: 82%
“…In some patients free of seizures, the feeling of being cured may lead to a cessation of treatment intake, leading to the occurrence of DRPs 18,43 . A previous study assessing the attitudes of Lebanese PWE towards their ASD, showed that some of them may stop their treatment in the seizure‐free period 14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations